Dose Selection for Induced Breeding and Larval Development of Indigenous Ornamental Fish Puntius chola (Hamilton, 1822) - Angsuman Chanda; Sanjat Kumar Sahu; Arun Jana; Godhuli Sit (Aquatic Sciences and Engineering, 2023)
Puntius chola (Hamilton, 1822) is a small freshwater indigenous fish with food and ornamental value belonging to the family Cyprinidae found in Pakistan, India, Nepal, Bangladesh, Myanmar, and Sri Lanka. Due to the selective exotic species and the culture of Indian big carp, the species have gradually diminished in India. Evaluating P. chola's optimum selection, induced breeding, embryonic, and larval development is the goal of the current study. The optimum dose was selected through the trial-and-error method applied 5 doses (0.25 ml/kg, 0.50 ml/kg, 1 ml/kg, 1.5 ml/kg, 2 ml/kg body weight) of synthetic hormone, ovatide to both sexes. The study reveals that the optimum dose of synthetic hormone ovatide @ 1.5 ml/kg body weight for females and males is effective for induced breeding of Puntius chola. At the optimum dose, fecundity, fertilization, and hatching rates were 106308±3075, 79.28±0.589%, and 78.03±0.495%, respectively. The physicochemical parameters of water have been enlisted for proper induced breeding. The outcomes of this research will enable P. chola to have a more decorative design and assist in its protection by encouraging it to reproduce and survive on its own in the wild. Additionally, the study will aid in community members' economic development.